STUDI KOMPARATIF TUGAS DAN FUNGSI PRESIDEN DALAM SISTEM KETATANEGARAAN SEBELUM DAN SESUDAH AMANDEMEN UUD 1945 - Rindawan, I Ketut (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2018)
Abstract This study aims to find out how the duties and functions of the president of the Republic of Indonesia according to the 1945 Constitution before and after the amendment and how differences in the Indonesian constitutional system before and after the amendments to the 1945 Constitution and to deepen the study material on Constitutional Law courses for students. In this study using descriptive, qualitative and literature study methods, where the data obtained were then analyzed from the prevailing laws and regulations. After being analyzed, the results of data analysis will be realized in the form of concise and clear data so that it is easy to understand. The results of the study show that the duties and powers of the president according to the 1945 Constitution after the amendment are the President of the Republic of Indonesia holding the power of the government of the country according to the Constitution. Thus the president functions as head of state and head of government. The fact that the function of the president as head of state can be seen from the elucidation of articles 10 to 15 which states that the power of the president as head of state. Whereas regarding the mechanism of accountability of the president in the 1945 Constitution, the President who is directly elected by the people through a general election is responsible for his performance and duties in his tenure according to the mandate and mandate of the state based on the applicable Law. Keywords: Tasks and Functions of the President, Before and After the Amendment of the 1945 Constitution of the Republic of IndonesiaAbstrakPenelitian ini bertujuan untuk mengetahui tugas dan fungsi presiden Republik Indonesia menurut UUD 1945 sebelum dan setelah amandemen dan bagaimana perbedaan sistem ketatanegaraan Indonesia sebelum dan setelah amandemen UUD 1945 dan untuk memperdalam bahan kajian mata kuliah Hukum Tata Negara bagi mahasiswa. Dalam penelitian ini menggunakan metode deskriptif, kualitatif dan studi pustaka, dimana data yang diperoleh kemudian dianalisis dari sudut perundang-undangan yang berlaku. Setelah dianalisis selanjutnya hasil analisis data akan diwujudkan dalam bentuk data yang ringkas dan jelas sehingga mudah dipahami. Hasil penelitian menunjukkan bahwa tugas dan kekuasaan presiden menurut UUD 1945 setelah amandemen adalah Presiden Republik Indonesia memegang kekuasaan pemerintahan negara menurut Undang-Undang Dasar. Dengan demikian presiden berfungsi sebagai kepala negara dan kepala pemerintahan. Kenyataan fungsi presiden sebagai kepala negara dapat dilihat dari penjelasan pasal 10 sampai pasal 15 yang menyatakan bahwa kekuasaan presiden sebagai kepala negara. Sedangkan mengenai mekanisme pertanggungjawaban presiden dalam UUD 1945 adalah presiden yang dipilih langsung oleh rakyat melalui suatu pemilihan umum bertanggungjawab terhadap kinerja dan tugasnya dalam masa jabatanya sesuai mandat dan amanat negara berdasarkan Undang-Undang yang berlaku. Kata kunci : Tugas dan Fungsi Presiden, Sebelum dan Sesudah Amandemen UUD RI 1945